Apples Supply Chain Strategy Influence on the Consumers to Buy Apples Products - Bob Foster (International Journal of Supply Chain Management, 2020)
Abstract One key aspect of Apple’s supply chain is its use of multiple suppliers for the same component. Reviews on this aspect of Apple’s supply chain strategy to examine the role that boards and directors can play in enhancing supply chain management and organisational performance that are prioritized in the electronic business competition. Increasing new smartphone vendors and creating smartphone products with advantages over other brands will cause consumers to recognize products according to their needs. This study aims to analyse the power of electronic word–of-mouth (eWOM) on supply chain procedure for trust and its impact on buying the interest of iPhone smartphones among customers. This research used the descriptive method and PLS path analysis. The population in this research was all consumers who are in the Bandung Electronic Center (BEC) with samples collection using an iteration formula. The study samples were 116 respondents. The results of this study explain that eWOM affects the supply chain and brand trust by 16.9% and 11.4% and the rest is influenced by other variables not examined in this study.